Programa jogos sensoriais para a educação infantil: percepção e desenvolvimento bioecológico - França, Ana Raquel de Oliveira (2016)
This paper aims at analyzing the pedagogical proposal of the Sensorial Games for Early childhood education Program (ProJsei), which applied the Pedagogy of Embodiment (PC) to early childhood education, between the years 2008 and 2014. The theoretical references are based on the Perception-Action Ecological Theory and on the Bioecological Human Development Theory, which helped to guide the discussions about the methodology used in the Pedagogy of Embodiment. The ProJsei program was analyzed within the context of regular school physical education, based on data collected from the projects, 12 reports and 8 semi-structured interviews with people who took part in the ProJsei program over the period defined in 4 public schools in João Pessoa. The data collected was analyzed taking into consideration some analytical categories (Content Analysis) that we defined: objectives (aims), theoretical reference adopted (concepts), methodology (procedures) and results (effects). We identified types of knowledge related to the five senses of the participants of the ProJsei; we discussed the teaching-learning methodology that was developed by members of the program, and we examined the patterns of learning achieved by the children involved. The study has shown that the projects, departing from the objectives/aims defined, could expand children’s awareness in relation to themselves and to their environment. All lessons followed the phases proposed by the Pedagogy of Embodiment, which used 95 games developed by teachers in initial education (PFI), involving 372 children participating in the ProJsei, along 188 classes, covering 170 hours of activities. In the scope of concepts/theoretical references, the academic projects, from 2011, involved specific activities for the senses and were directed to an ecological perspective, developing activities that expanded the relationship child-environment. In that sense, the teachers in initial education (PFI) showed understanding in relation to the Pedagogy of Embodiment (PC), but they revealed the need to build knowledge about the gibsonian and bronfenbrenian theories. When analyzing the procedures/methodology of the ProJsei, we noticed that the teachers in initial education (PFI) concentrated on the second moment of the Pedagogy of Embodiment Lab Class (ALPC), using as resource the diagnostic evaluation data. We perceived that the microsystem has influence on the choice of games by the teachers (PFI) and that children could express what they learned more easily through drawings than orally. As for the effects/results of the ProJsei, the PFI reported that there was sensorial amplification of participants: in sight, they expanded the concept of primary colors and their nuances, in addition to the perception of the environment. In chemosensory projects, like taste, they took more pleasure in tasting and accepting food that were previously rejected; in terms of smell, they built some knowledge in relation to spicy and putrid scents and in the sensorial manipulative project – touch, they got better performance in the thermal category and in texture; in hearing, there was improvement in performance in terms of accoustic location and, in small scale, in relation to sequential memory, in addition to developing more sensitivity in the environment perception. We may say that the ProJsei stands as a pedagogical alternative for the application of PC in Early Childhood education, in spite of the fact that pedagogical improvements are required. The ProJsei promotes the access of students to the world of movement, not only in relation to perceptual motor abilities, but also in terms of communication with oneself, with others and with the world.